Epidemiology of antimicrobial resistance in Lebanese extra-hospital settings: An overview. (June 2019) - Osman, Marwan; Al Mir, Hiba; Rafei, Rayane; Dabboussi, Fouad; Madec, Jean-Yves; Haenni, Marisa; Hamze, Monzer
Highlights: Antimicrobial resistance (AMR) is highly worrisome in Lebanese non-clinical settings. Animals, foodstuffs and the environment are significant reservoirs of AMR in Lebanon. Multi- and extensively-drug-resistant Gram-negative bacilli are ubiquitous in Lebanon. Dissemination of resistant clones in the community may have a zoonotic origin. Abstract: Antibiotics can truly be considered the symbol of the 20th century's miracle drugs. However, excessive and inappropriate use of antibiotics in human and veterinary medicine has led to repercussions in terms of mortality, morbidity, and financial and societal costs, especially with the lack of novel drugs to combat infections caused by antimicrobial-resistant pathogens. Unfortunately, antimicrobial resistance (AMR) has increased significantly worldwide in the past decades, particularly in developing third-world countries. Hence, various key organisations have made AMR the focus of highly visible reports, conferences and actions. Nevertheless, the majority of investigations were initiated in the developed world. In Lebanon, as in other developing countries, AMR remains responsible for significant morbidity and mortality. Whilst a large number of studies have targeted the AMR crisis in Lebanese clinical settings, its epidemiological situation in animals, foodstuffs and the environment is still unclear in this country. In this context, and in order to better survey, control and prevent the emergence of multidrug-resistant bacterial strains in Lebanese non-clinical settings, this work reviewed the available data on the epidemiology of antimicrobial-resistant bacteria isolated from Lebanese extra-hospital sources.